Wnt/β-Catenin Pathway Balances Scaffold Degradation and Bone Formation in Tissue-Engineered Laminae. (13th September 2021) - Li, Hailong; Li, Linli; He, Yiqun; Mao, Wei; Ni, Haofei; Yang, Aolei; Lyu, Feizhou; Dong, Youhai
Abstract : Tissue engineering provides a promising way for the regeneration of artificial vertebral laminae. Previous studies have confirmed the feasibility of reconstructing vertebral laminae via hydroxyapatite-collagen I scaffolds and mesenchymal stromal cells. However, there were no studies exploring the degradation of hydroxyapatite-collagen I scaffolds and the function of Wnt/ β -catenin pathway in the process. In this study, tissue-engineered laminae (TEL) were constructed by nanohydroxyapatite/collagen I scaffolds and umbilical cord Wharton's Jelly mesenchymal stromal cells (WJ-MSCs). Cell attachment was observed by scanning electron microscopy, and cell viability was confirmed by Live/Dead staining. The rat models were randomly divided into control and β -catenin inhibition groups. Vertebral lamina defect rat models were made on the fifth lumbar vertebrate, and TEL was implanted into the defect site. After 14 weeks, the newborn laminae were harvested for microcomputed tomography, histology, or transcriptional profile analysis. We found that, for the control group, the newborn lamina formation matched with the scaffold degradation and complete newborn laminae formed at the 14th week; for the β -catenin inhibition group, the scaffold degradation rate overrated the lamina formation and no complete artificial laminae were formed at the 14th week. In addition, the osteoclastic genes, such as Cathepsin K or RANKL, in the control groups were significantly lower than the β -catenin inhibition group, and the antiosteoclastic gene, OPG, in the control group was significantly higher than the β -catenin inhibition group. In conclusion, inhibition of Wnt/ β -catenin pathway led to speedy scaffold degradation and deferred artificial lamina formation. Wnt/ β -catenin pathway played a critical role in maintaining the balance between scaffold degradation and bone formation in the process of vertebral lamina reconstruction.